2011
DOI: 10.1080/ac.66.2.2071246
|View full text |Cite
|
Sign up to set email alerts
|

Heart structure and function in patients with generalized autoimmune diseases: echocardiography with tissue Doppler study

Abstract: Echocardiography with TDE reveals characteristic pathology in different forms of generalized autoimmune diseases reflecting their different pathogenetic mechanisms. Overproduction of collagen in SSc results in diastolic left ventricular dysfunction, while generalized inflammation in SLE and DPM leads mainly to pathologic changes on valvular leaflets and/or pericardium. Interestingly, right ventricular dysfunction is common in all diseases analyzed, regardless of the presence of pulmonary hypertension. Echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…Di erent diseases may act on the cardiovascular system through the activity of mediators of in ammation. [12][13][14] A similar association is also found between in ammation and supraventricular arrhythmias. [15] Although data about how cardiovascular system is a ected in SS is limited, le ventricular systolic and diastolic dysfunction, pericardial e usion, pulmonary hypertension and valvular dysfunction have all been reported in patients with SS.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Di erent diseases may act on the cardiovascular system through the activity of mediators of in ammation. [12][13][14] A similar association is also found between in ammation and supraventricular arrhythmias. [15] Although data about how cardiovascular system is a ected in SS is limited, le ventricular systolic and diastolic dysfunction, pericardial e usion, pulmonary hypertension and valvular dysfunction have all been reported in patients with SS.…”
supporting
confidence: 56%
“…Myocardial dysfunction can be a result of myocarditis, myocardial brosis, vasculitis or microvascular dysfunction in these patients, but it can also be secondary to general subclinical or clinical in ammatory status. [14,[23][24][25][26] Liang et al showed that diastolic dysfunction is much more prevelant in patients with RA and they concluded that this may potentially be due to chronic autoimmune in ammation. [27] ey found a signi cant relationship between IL-6 and le ventricular diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothesis: More attention will be focused on the heart in PM/DM as we would have wished, which contribute to improve the prognosis. Methods: All articles published in English were retrieved by searching MEDLINE via PubMed (1975-2011. After selecting eligible articles according to the predefined inclusion and exclusion criteria, a systemic review was carried out.…”
mentioning
confidence: 99%
“…-у 32% больных ССД. Некоторые авторы считают, что ДД при ССД связана с гиперпродукцией коллагена [27]. M. D'Alto и соавт.…”
Section: параметр врс число больных N (%)unclassified